Cellular and molecular aspects at invasive tumor front in oral squamous cell carcinoma (part-I) - Rekha Bhaskar Chaudhari (SRM Journal of Research in Dental Sciences, 2016)
Oral squamous cell carcinoma (OSCC) is one of the leading cancers in India and Asian countries. Tumorigenesis has been linked to abnormalities in molecular regulatory machinery. Traditional factors such as tumor size, neck node status, and presence of distant metastasis staging, histological grading, and depth of invasion are currently used to predict the outcome of OSCC. However, these seem to be of limited value. Recent work indicates that morphological and molecular characteristics of tumor cells at invasive tumor front (ITF) underlie biological aggressiveness of oral cancer. Recent advances in molecular biology have facilitated analysis of the critical component of cancer progression. The degree of expression of various molecules provides reliable prognostic and predictive information. Predicting prognosis and clinical outcome of patient is very important for developing an effective therapeutic strategy. This paper provides an overview of the cellular activities and molecular interactions of the complex biology of tumor progression, invasion, and metastasis with focus on ITF.